Perkecambahan Biji dan Pertumbuhan Semai Tanaman Jarak Pagar (Jatropha Curcas L.) - Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
The physics nut ( Jatropha Curcas L.) is an economic crop which widely cultivated in the tropics. This plant productivity is very depended from some factors like genetic, cultivation and environmental. One important step in supporting of good physics nut cultivation is in seedling phase that is ready of good quality seed will very determine on efficacy. This research was carried out to investigate the germination of seed and growth of physics nut seedling. The research consists of two experiments with purposes: 1. to investigate the percentage of germination of physics nut seed from Lampung and Mataram on different media; 2. to investigate the seedling growth of physics nut on different of media and percentage of light shading during two months. The result showed that seed from Mataram have higher percentage of germination ( 61-65 %) than from Lampung        ( 25 - 39%). The physics nut seedling which is planted on media mixture beetwen soil and fertilize cage 1:1 and light shading of 40% yielding the quality of best growth